2020
DOI: 10.1111/ced.14180
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biologics targeting interleukin‐23/‐17 axis on subclinical atherosclerosis: results of a pilot study

Abstract: Summary Background Psoriasis is associated with an increased risk of developing atherosclerotic vascular disease. The hypothesis that treatment of the skin inflammation may decrease the risk of developing atherosclerosis and consequently, cardiovascular disease, is currently a focus of significant attention. Aim To assess the effect of biologic drugs targeting the interleukin (IL)‐23/IL‐17 axis on selected subclinical atherosclerosis parameters in patients with psoriatic disease. Methods In a series of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The improvements in patients' clinical characteristics are shown in Table 3. The median initial PASI value for the overall study population was 18 (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). After 6 months of treatment with anti-IL-17 therapies, the PASI score significantly decreased (p < 0.001) to a median value of 0 (0-4).…”
Section: Clinical Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The improvements in patients' clinical characteristics are shown in Table 3. The median initial PASI value for the overall study population was 18 (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). After 6 months of treatment with anti-IL-17 therapies, the PASI score significantly decreased (p < 0.001) to a median value of 0 (0-4).…”
Section: Clinical Findingsmentioning
confidence: 99%
“…In our previous study, we observed a significant improvement of the carotid and brachial IMT (bIMT) values among moderate-to-severe psoriatic patients after 6 months of TNF inhibitor treatment [ 9 , 13 ]. In contrast, other studies found no significant improvement in cIMT values by using ustekinumab, secukinumab, ixekizumab, and adalimumab therapies [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…These results demonstrated the effectiveness of ustekinumab in alleviating the symptoms of patients with moderate-to-severe Crohn’s disease [ 136 ]. A small-scale pilot study examined the atherosclerosis parameters in patients with psoriasis treated with ustekinumab, and reported that while there was a noticeable relief of skin lesions after 6 months of treatment, there was no notable change in the pulse wave velocity and intima-media thickness [ 137 ].…”
Section: Cytokine-targeting Therapymentioning
confidence: 99%
“…At present, the main inhibitors for the treatment of psoriasis are IL-23 inhibitors, IL-17 inhibitors, and TNF- α inhibitors. The central role of interleukin-23/interleukin-17 (IL-23/IL-17) axis in the pathogenesis of psoriasis and the effectiveness of its targeted therapy have been confirmed by numerous studies [ 6 , 7 ]. IL-23 belongs to the IL-12 cytokine family.…”
Section: Introductionmentioning
confidence: 99%